(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article presents new elements of technological adaptation of general-purpose tractors of imported production, the most in demand in the agricultural sector of Ukraine. A new algorithm of technological adaptation of the tillage unit implemented on winter wheat stubble by a New Holland tractor when aggregated with a DLM-8.0 huller is proposed. A new method of ballasting the tractor according to groups of the tillage technological process is proposed, which is based on determining the mass of the ballast. Experimentally, the statement that the use of ballast is effective to a certain increase in the speed of the tractor is proven on the John Deere 8400 tractor. The engine power consumption for tractor movement when moving without ballast / with ballast on different agro backgrounds is considered.